Performance and spermatogenesis of Nile tilapia fingerlings fed with cottonseed meal or cottonseed flour - Salaro, Ana Lúcia; Pezzato, Luiz Edivaldo; Barros, Margarida Maria; Vicentini, Carlos Alberto (Pesquisa Agropecuaria Brasileira, 1999)
This experiment evaluated the effect of cottonseed meal or cottonseed flour on growth and testis activity of Nile tilapia fingerlings (Oreochromis niloticus). One hundred and fifty fingerlings with mean initial weight of 1.26 g were maintained in 45 L aquaria with continuous water supply. Fish were fed in isoproteic (28% CP) and isoenergetic (4,030 kcal CE/kg of ration) diets during 120 days. The experimental diets comprised a control diet, without cottonseed flour or meal, and diets containing 2%, 4% and 6% of cottonseed flour and 24% cottonseed meal. The results indicated that the use of seed flour or meal should be limited since at the tested levels they interferred with testis activity although they had not adversely affected the weight gain of fingerlings.